Appraising the unhappiness due to the Great East Japan Earthquake: Evidence from weekly panel data on subjective well-being - Fumio Ohtake; Katsunori Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2013)
After severe disasters, persons living not only in the directly affected areas, but also in distant areas could be seriously affected thorough images of the disaster on television and in newspapers. Hence, it can be difficult to define qualified beneficiaries for policy compensation in terms of psychological suffering. Building on the case of Great East Japan Earthquake, we appraise psychological suffering from disaster-related news through the experienced utility approach. We take advantage of the serendipitous timing of our original nationwide weekly panel survey that became a timely investigation of subjective well-being in the immediate aftermath of the earthquake. Although a pale was cast over the whole society, we found that there was a robust and large geographical heterogeneity between the disaster area and non-disaster areas in mental costs. This finding may capture the focusing effect, suggesting that resources for compensating mental suffering should be concentrated on persons living in the disaster area.
Keywords: I31; H56; D61; 330; Great East Japan Earthquake; subjective well-being; experienced utility approach; focusing effect; high frequency panel data; Erdbeben; Katastrophenschaden; Zufriedenheit; Meinung; Panelforschung; Japan